2021
DOI: 10.1007/s11002-021-09573-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of augmented reality versus traditional advertising: a comparison between neurophysiological and self-reported measures

Abstract: Despite the growing application of augmented reality in advertising, there is limited understanding about how customers respond to their interaction with the augmented reality advertising and how it differs from a standard paper-based advertising. Augmented reality ads are immersive, interactive, and lifelike, which means they may help companies create an emotional connection with their customers. The authors test if customers would respond in terms of emotional and affective intensity differently to augmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 46 publications
0
24
0
1
Order By: Relevance
“…Wang et al (2020, p. 1) argued that people use emotions to make “colored” judgments that influence their attitudes and behaviors. Pozharliev et al (2021) investigated the intensity of emotional responses in the AR context and found that AR advertisements may enhance users' physiological responses (in the form of arousal) as well as influence their willingness to pay.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2020, p. 1) argued that people use emotions to make “colored” judgments that influence their attitudes and behaviors. Pozharliev et al (2021) investigated the intensity of emotional responses in the AR context and found that AR advertisements may enhance users' physiological responses (in the form of arousal) as well as influence their willingness to pay.…”
Section: Introductionmentioning
confidence: 99%
“…Second, it contributes to the literature on the role of message characteristics in determining the effectiveness of a brand-related message posted on social platform (Balabanis and Chatzopoulou, 2019;Balaji et al, 2021;Lee and Theokary, 2021;Lou and Yuan, 2019;Uribe et al, 2016;Xiao et al, 2018) by testing if argument quality affects consumer responses to advertising message posted by micro-versus meso-influencers. Third, the study findings contribute to the growing body of literature that seeks to understand how neurophysiological processes affect online experiences and customer responses to online marketing communication (Lin et al, 2018a(Lin et al, , 2018bPozharliev et al, 2022) Finally, our research also offers practical implications for marketing managers and SMIs looking for insights on how to enhance the credibility of their online communication, particularly for those marketers interested in empirical evidence to support their decision to invest in social media marketing. Our results suggest that marketers should carefully consider Instagram influencers based on the trade-offs between credibility and reach.…”
Section: Advertising Post On Instagrammentioning
confidence: 70%
“…with recent consumer neuroscience studies that have clearly suggested that researchers and marketers should disentangle the different types of responses (i.e. self-reported vs neurophysiological) that SMIs' messages might elicit in consumers (Pozharliev et al, 2022;Royo et al, 2018). Therefore, in the current study, we use consumer neuroscience, namely, electroencephalogram (EEG) brain responses, to assess the level of consumer cognitive work associated with the processing of an advertising message presenting weak (vs strong) argument quality and posted by SMIs with relatively higher or lower numbers of followers.…”
Section: Advertising Post On Instagrammentioning
confidence: 99%
“…Marketing communication research describes the benefits of a consumer neuroscience research approach, highlighting how it allows greater inferential traction and more reliable measurement than traditional self-reported markers of advertising effectiveness (Casado-Aranda et al, 2021;dos Santos et al, 2015;Sánchez-Fernández et al, 2021). This idea resonates with recent consumer neuroscience studies that have clearly suggested that researchers and marketers should disentangle the different types of responses (i.e., self-reported vs. neurophysiological) that an advertising message might elicit in consumers (Casado-Aranda et al, 2020;Pozharliev et al, 2021a). Therefore, in the current study we use consumer neuroscience, namely eye-tracking and electroencephalogram (hereafter EEG), to assess the level of consumer responses to advertising message presenting weak (vs. strong) argument quality and posted by social media influencers with relatively higher or lower numbers of followers.…”
mentioning
confidence: 95%